2021
DOI: 10.3329/bjb.v50i1.52672
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of α-glucosidase inhibition, antioxidant and antibacterial effects of Gymnema sylvestre R. Br.

Abstract: The results of antioxidant assays with Gymnema sylvestre leaf extracts revealed that methanol, acetone, and aqueous extracts possessed maximum DPPH (83, 83, and 75%) and ABTS scavenging potential (85, 71, and 82%). Chloroform possessed maximum total flavonoid (24.6 mg/100 ml) and total iron contents (435.3 ± 0.0125 mg FeSO4 E/G). The extracts of n-hexane, ethyl acetate, and chloroform of Gymnema sylvestre leaves displayed an IC50 value of 170.2, 44.4, 131.6 μg/ml, respectively in α-glucosidase inhibition assay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…This indicates its ability to neutralize DPPH free radicals. On the other hand, Subramanian et al 23 , Fazal et al 63 , Ghous et al 64 and Jeytawan et al 62 obtained radical scavenging activity of 73.4, 54.4, 83.0 and 62.6% respectively (Table 3 ). Jeytawan et al 62 stated that antioxidant capacity of processed leaves was higher when compared to fresh leaves.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…This indicates its ability to neutralize DPPH free radicals. On the other hand, Subramanian et al 23 , Fazal et al 63 , Ghous et al 64 and Jeytawan et al 62 obtained radical scavenging activity of 73.4, 54.4, 83.0 and 62.6% respectively (Table 3 ). Jeytawan et al 62 stated that antioxidant capacity of processed leaves was higher when compared to fresh leaves.…”
Section: Discussionmentioning
confidence: 94%
“…Table 3 compares the antioxidant potential of PCD extract powder prepared with 0.5% ( w/v ) maltodextrin with that of Gymnema extracts by others research 23 , 62 64 . From the results of present study, it was found that PCD extract powder was able to neutralize 75.8% ± 2.6 of DPPH free radicals at 1.58 mg/mL concentration.…”
Section: Resultsmentioning
confidence: 99%
“…This suggests that Distichochlamys citrea n ‐hexane fraction seems to be specifically efficacious for inhibition of Streptococcus pyogenes . In addition, some other efforts found that n ‐hexane extracts of Gymnema sylvestre leaves, [33] Carissa edulis leaves, [34] Suaeda vermicuata [35] were inactive against Streptococcus pyogenes , which suggest the correlation between the inhibitability and the content of terpene in the different plant species [36] . Furthermore, in‐depth attempts are needed to evaluate the antibacterial potential of sub‐fractionated extracts of Distichochlamys citrea .…”
Section: Discussionmentioning
confidence: 99%
“…Afterward, the dishes were incubated (duration 24 h; temperature 37 °C) before the inhibition zone diameter (IZD) was measured. 25 The procedure was in triplicate in order for the mean IZD to be determined 26,27 and interpreted as 0 mm for no sensitivity or resistance, 1–6 mm for low sensitivity, 7–14 mm for moderate sensitivity, and >14 for high sensitivity.…”
Section: Methodsmentioning
confidence: 99%